Life tables of Toxorhynchites rutilus (Diptera: Culicidae) in nature in Southern Florida - Campos, Raul Ernesto (2000)
Stage-specific survivorship curves were constructed for the immature stages of a native, predatory mosquito, Toxorhynchites rutilus (Coquillet), by regular censuses in the summer and fall of water-holding treeholes and tires. Survival from egg to adult ranged from 1.8 to 5.6%, and survivorship patterns were significantly heterogeneous between seasons and container types. The probability of death was highest in the first and fourth larval instars. Rainfall and drought were relatively unimportant risk factors during this study, but the probabilities of disappearance of eggs and first and fourth instars were significantly higher in the presence of large conspecifics, suggesting that cannibalism is a major source of mortality.